A Decision-Support Analytics Framework of Strategic HR Practices and Employee Performance in Islamic Banking - Melyani, Melyani; Yulianto, Yulianto; Nikmah, Wasilatun; Armaniah, Henny; Subariyanti, Herudini; Yulianto, Andri Rizko; Daniel, Daniel (University of Science and Computer Technology, 2026)
This research analyzes Islamic banking's strategic human resource strategies by examining how compensation, work incentives, and job satisfaction affect employee performance. 210 Islamic finance personnel were quantitatively surveyed and evaluated using Partial Least Squares–Structural Equation Modeling (PLS-SEM) using SmartPLS. Bootstrapping. 5,000 subsamples were used to evaluate direct and indirect impacts. Research indicates that financial remuneration and work motivation negatively affect employee performance (β = −0.280 and β = −0.182, respectively). Job happiness has a low but positive impact on employee performance (β = 0.087). Minimal indirect effects and variation accounted for (VAF) values below 20%. Job satisfaction does not moderate the links between financial compensation and employee performance, nor between work motivation and performance. The findings suggest that direct processes, rather than emotional measures such as job happiness, affect the performance of Islamic banking employees. The Islamic banking strategic human resource management literature is enhanced by emotional assessments, such as job satisfaction. Strategic human resource management in Islamic banking is informed by research, with managerial implications for fair remuneration systems and sustainable motivational techniques that reflect Islamic ideals.